PRELIMINARY SCREENING OF PHYTOCHEMICAL AND MINERAL CONTENT OF CHLOROFORM AND METHANOL EXTRACTS OF STRYCHNOS NUX VOMICA L AND OPHIORRHIZA RUGOSA WALL - BHAVYA D. K; KRISHNAMOORTHY M (International Journal of Pharma and Bio Sciences, 2014)
Medicinal plants are the nature gifts to human to lead disease free healthy life. The examination of plants for bioactive secondary metabolites is an area which most scientist have recently focused. Strychnous nux vomica L(SNV) and Ophiorrhiza rugosa Wall(OR) are endangered plants of the family Loganiaceae and Rubiaceae respectively .In the present study they were analyzed for their phytochemical constituents and minerals. The study revealed the presence of alkaloids, phenols, flavonoids by qualitative analysis. The total phenolic content was 0.143mg and 0.3297mg/mg respectively in the methanol extract of S.nux vomica and chloroform extract of O.rugosa. Mineral analysis showed the presence of Fe, Na, Mg, Mn, Zn and Cu in both the plants and Cd and Pb are absent in both the plants.